Reconceptualizing Quranic Narratives: A Study of Intertextual Approaches in Western Academia - Zulhamdani, Zulhamdani; Hussin, Md. Noor bin (ZAD Al-Mufassirin, 2025)
The shift in Western scholarship on Quranic studies through an intertextual approach marks a significant development in appreciating the Quran as an independent text, not merely based on the borrowing theory proposed by earlier Western scholars. This study explores how contemporary Western scholars use intertextual approaches, including Brannon Wheeler, A.H. Johns, Angelika Neuwirth, and Sidney Griffith. Specifically, it focuses on their analysis of Qur`anic narratives. This study adopts a qualitative approach. It bridges theoretical insights with practical analysis by reviewing key literature from Western scholars, focusing on Quranic narratives and their intertextual connections. The main findings of this study reveal that these scholars reject the simplistic borrowing theory and emphasize the Quran's re-conceptualization and reinterpretation of previous traditions. Their works illustrate how intertextuality deepens the understanding of the Quran as a dynamic text engaged in a broader religious dialogue.